Ancient Akkadian Grammatical Concepts - Dietel, Robert Grayson
Ph.D. Dissertation; Chairman: F. J. Newmeyer. Order No. DA8706538; cf. DissAbstr 47/12 (June 1987) 4375-A; mainly on OB/NB Grammatical and Edubba Texts